Oxigenoterapia hiperbárica como adjuvante no tratamento de sepse pelo complexo hiperplasia endometrial cística-piometra em cães - Degregori, Emanuelle Bortolotto (2024)
The objective of this research was to evaluate the effects of hyperbaric oxygen therapy (HBOT) when used in the postoperative (PO) period of ovariohysterectomy (OVH) in dogs diagnosed with Cystic Endometrial Hyperplasia-Pyometra Complex (CEM-P) and sepsis. Eighteen female dogs previously diagnosed with CEM-P and in sepsis according to the criteria of Systemic Inflammatory Response Syndrome were included in this study. After random distribution, the animals were allocated into two groups: control group (CG, underwent to OVH associated with supportive therapies) and hyperbaric group (HG, underwent to OVH associated with supportive therapies, in addition to three sessions of HBOT under a protocol of 2 ATA for 45 minutes, started immediately after surgical correction). Hematological, biochemical, lactate and glycemic analyses were performed at T0 (admission), T1 (immediate PO), T2 (PO 24h), T3 (PO 48h), T4 (PO 72h) in all patients. Assessments of physical parameters were performed at the same time points in CG and HG. In the latter, the parameters were collected again at the end of each hyperbaric session. During all sessions, the animals were monitored and information about their behavior was compiled. Some patients became agitated during HBO sessions, but were not relevant to interrupt the sessions. No variables differed between groups. RT decreased between T0 and T1 in CG (0.0234) and remained reduced in HG during all assessments when compared to T0 (T1: 0.0489; T2: 0.0225; T3: 0.0045; T4: 0.0014), but did not differ before and after sessions. There was no statistical difference in the other physical parameters. Lactate showed a considerable reduction between T0 and T3 and T4 (0.0004; 0.0135) and between T2 and T3 (0.0224) in the CG; and between T0 and T3 and T4 (0.0224; 0.0135) and T2 and T4 (0.462) in the HG. There was no difference in the glycemic dosage. Both groups showed a significant reduction in red blood cells and hematocrit equivalent to T0. However, at discharge, only HG increased the overall mean and did not differ from baseline. Despite the significant reduction in hemoglobin after one (0.0462) and two (0.0365) HBO sessions, at T4 the variable reestablished a value similar to baseline. A substantial decrease of 50% in leukocytes was observed in HG at T4 compared to T0 (0.0035) and T2 (0.0001). In addition, a statistical difference in HG was observed in the reduction of neutrophils, rods and absence of metamyelocytes after two HBO sessions. It is concluded that HBO is acceptable and safe for patients when initiated in the immediate postoperative period. Caution should be exercised when using the therapy in patients with low temperatures, as hypothermia tends to persist. Lactate reduction may take up to three days to begin, but there is no worsening of prognosis or longer hospitalization time. Three HBO sessions associated with HBO and supportive therapy can be considered in the treatment of pyometra, improving the anemic condition and accelerating the immune response, quickly reestablishing control of the infectious process.